2015
DOI: 10.1016/j.jecp.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal development of number line estimation and mathematics performance in primary school children

Abstract: Children's ability to relate number to a continuous quantity abstraction visualized as a number line is widely accepted to be predictive of mathematics achievement. However, a debate has emerged with respect to how children's placements are distributed on this number line across development. In the current study, different models were applied to children's longitudinal number placement data to get more insight into the development of number line representations in kindergarten and early primary school years. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
75
0
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 48 publications
7
75
0
12
Order By: Relevance
“…Reversing the order by which variables were entered into the hierarchical regression (i.e. by first entering the number line estimation metrics and then entering the visuo-spatial and visuo-motor integration component variable scores; (Booth & Siegler, 2008;Muldoon et al, 2013;Siegler & Opfer, 2008;van den Bos et al, 2015). It was also observed that there were medium to strong significant correlations between all visuo-spatial and visuo-motor integration measures and number line estimation, barring between R 2 LIN and both visuo-spatial working memory and mental rotation.…”
Section: Creation Of Component Variables From Visuo-motor Integrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Reversing the order by which variables were entered into the hierarchical regression (i.e. by first entering the number line estimation metrics and then entering the visuo-spatial and visuo-motor integration component variable scores; (Booth & Siegler, 2008;Muldoon et al, 2013;Siegler & Opfer, 2008;van den Bos et al, 2015). It was also observed that there were medium to strong significant correlations between all visuo-spatial and visuo-motor integration measures and number line estimation, barring between R 2 LIN and both visuo-spatial working memory and mental rotation.…”
Section: Creation Of Component Variables From Visuo-motor Integrationmentioning
confidence: 99%
“…A number of tasks have been used to provide an indication of the precision of individuals' numerical representations, of which the number line estimation task is a popular measure (Geary, Hoard, Nugent, & Byrd-Craven, 2008, Siegler & Opfer, 2003van den Bos et al, 2015). In a number line estimation task, participants are generally presented with number lines which include the value of the start and end point of the scale (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In general, authors agree that numeracy performance in the early childhood years adequately predicts later mathematics performance (Jordan, Glutting & Ramineni 2010). Especially magnitude comparison, number reading, counting skills, basic arithmetical skills, number line acuity, spontaneous focusing on numerosity and numeracy-related logical knowledge have been found to be relevant for later mathematics performance (Aunio & Niemivirta 2010;Friso-van den Bos et al 2015;HannulaSormunen, Lehtinen & Räsänen 2015;Jordan et al 2010;Krajewski & Schneider 2009;LeFevre et al 2010;Nguyen et al 2016;Passolunghi, Vercelloni & Schadee 2007;Toll et al 2015;Vanbinst, Ghesquière & De Smedt 2015). Related to the development of mathematical skills in early childhood years, there is an agreement among the researchers that children have biologically primary non-verbal number sense which is the base that children start to learn to use their number word sequence skills first in rhymes and then in enumeration tasks and from that follows the basic strategies for addition and subtraction problem solving (Jordan et al 2010;Mazzocco, Feigenson & Halberda 2011).…”
Section: Early Numeracy Skills Relevant For Later Mathematics Learningmentioning
confidence: 94%
“…It is currently debated whether number line estimation tasks tap into children's internal number representation (the mental number line), or whether it reflects proportion judgement strategies (see Dackermann, Huber, Bahnmueller, Nuerk, & Moeller, 2015 for a review on this topic). Nevertheless, performance on the number line estimation task has been consistently related to later mathematical achievement making it a relevant measure of mathematical development (Ashcraft & Moore, 2012;Booth & Siegler, 2008;Friso-van den Bos et al, 2015;LeFevre et al, 2013;Siegler & Opfer, 2003;Simms et al, 2016).…”
Section: The Present Studymentioning
confidence: 99%